Delineating the relationship between maritime insecurity and COVID-19 pandemic on West African maritime trade - Anthony Djaba Sackey; Bernard Lomotey; Abigail Dede Sackey; Raphael Ofosu-Dua Lee; Abraham Akwetey Teye; Richmond Kennedy Quarcoo; John Bansah (Journal of Shipping and Trade, 2022)
Abstract In this paper, three steps are made. First, an effort is made to show a consequential effect of maritime insecurity on seafarers and marine professionals; they are at risk of a complicated string of processes that impact their lives. Second, there is the risk to the environment and property. Third, the economic cost of traditional maritime crimes is examined against the potential maritime trade expansion from implementing the African Continental Free Trade Area (AfCFTA). Third, the policy and regulatory measures implemented in the region against piracy are assessed to propose additional measures for improvement. Essentially, the study deploys a case study approach with a three-year field observation over the Gulf of Guinea region and is supported by outcomes of various remote interviews, in addition to online surveys conducted over three months—findings are juxtaposed with the estimated cost of piracy and potential implications for policies driving economic advancement. The results showed inadequate maritime surveillance despite enormous legal frameworks amidst the current structures of regional and international corporations. The piracy cost is high and inevitable as a factor of insurance coverage passed onto end consumers. Response to piracy has been reactionary rather than proactive, as attacks have continued in territorial and offshore areas into 2021. The impact will be visible on AfCFTA post-COVID-19. The study highlights the need for a community-based approach to surveillance modelled after the community policing model currently implemented in Ghana.